Investor sentiment, market volatility, and ESG Index dynamics: an empirical analysis - Pushpa Negi; Silky Vigg Kushwah; Anand Jaiswal; Ihor Rekunenko (Cogent Economics & Finance)
This study integrates both traditional finance theory and behavioral finance to explore the impact of investor sentiment and market volatility on Environmental, Social and Governance (ESG) thematic indices in the Indian market. Using the India Volatility Index to represent market volatility and the Market Mood Index as a measure of investor sentiment, the research examines three ESG indices from the National Stock Exchange: the Nifty 100 ESG Index, the Nifty 100 Enhanced ESG Index and the Nifty 100 ESG Sector Leaders Index. Daily data from April 2018 to May 2024 is analyzed through a quantile causality approach to investigate how these variables interact across different market conditions. Findings reveal that investor sentiment and market volatility deviate ESG stock returns from fundamental values, challenging the Efficient Market Hypothesis. The study underscores behavioral finance’s role in ESG performance, providing insights into resilient investments and sustainable policy stability.